Pengaruh Live Streaming, Shopping Lifestyle, dan Hedonic Shopping Value terhadap Impulsive Buying melalui TikTok Shop dengan Mediasi Price Discount pada Generasi Z - Adawiyah, Rafi'ah Al; Haris, Helmi (Jurnal Manajemen Bisnis dan Keuangan, 2024)
The rise of e-commerce, particularly TikTok Shop, has altered the shopping behavior of Generation Z, with live streaming features triggering impulsive buying. This study aims to analyze the influence of live streaming, shopping lifestyle, and hedonic shopping value on impulsive buying, with price discount as a mediating factor among TikTok Shop users in the Kangean Islands, Sumenep Regency. The research adopts a quantitative approach using Structural Equation Modeling Partial Least Squares (SEM-PLS) analysis through SmartPLS 3.0. The results show that live streaming and shopping lifestyle significantly influence price discount but have no direct impact on impulsive buying. Conversely, hedonic shopping value significantly affects impulsive buying but does not significantly influence price discount. Additionally, price discount does not have a significant effect on impulsive buying and does not serve as a significant mediator between the independent variables and impulsive buying. These findings highlight those emotional factors such as hedonic shopping value drive impulsive buying behavior more than price discounts. This study provides new insights for marketers and e-commerce platforms on the importance of emotional factors in influencing impulsive buying among Generation Z, along with practical implications for marketing strategies on TikTok Shop.